A new spacecraft mission concept combining the first exploration of the Centaurs and an astrophysical space telescope for the outer solar system. (1st October 2021) - Singer, Kelsi N.; Stern, S. Alan; Elliott, John; Karimi, Reza R.; Stern, Daniel; Chimelewski, Arthur B.; Fong, Michael J.; Andrews, John; Bottke, William F.; Olkin, Catherine B.; Propster, Paul; Thurman, Sam W.
Abstract: We present a concept study for a distinctive robotic spacecraft mission that combines both the exploration of a never-before-visited class of planetary bodies and cutting-edge astrophysical investigations. The planetary targets are a class of objects called Centaurs that have relatively recently escaped from the Kuiper Belt and currently orbit closer to the Sun among the giant planets. We developed a trajectory that would visit several Centaurs, including the second largest known Centaur, 2060 Chiron, which displays enigmatic coma activity at large heliocentric distances and orbiting ring or dust structures. This concept takes advantage of the cruise times between planetary encounters to conduct nearly continuous astrophysical observations at wavelengths that are not accessible by ground-based facilities. Additionally, ride-along cubesats included aboard can be deployed at different points in the mission to perform various experiments or observations. This mission concept achieves its objectives with solar power (MegaFlex arrays), no new technology development, and within the approximate budget of a NASA New Frontiers class mission. The mission design accomplishes its objectives using solar electric propulsion and the recently developed NASA Evolutionary Xenon Thruster (NEXT) ion engines. Highlights: This mission concept combines astrophysical, planetary, and cubesat science. The spacecraft would flyby the never-before visited Centaur population. The large ( 220 ​km diameter) Centaur Chiron is the principal flyby target. Astrophysical science would be conducted during much of the 10-year flight. The mission is accomplished with solar power and NASA NEXT ion engines.